Further corroboration of distinct functional features in SCN2A variants causing intellectual disability or epileptic phenotypes - Anaïs Begemann; Mario A. Acuña; Markus Zweier; Marie Vincent; Katharina Steindl; Ruxandra Bachmann-Gagescu; Annette Hackenberg; Lucia Abela; Barbara Plecko; Judith Kroell-Seger; Alessandra Baumer; Kazuhiro Yamakawa; et al. (BMC, 2019)
Abstract Background Deleterious variants in the voltage-gated sodium channel type 2 (Nav1.2) lead to a broad spectrum of phenotypes ranging from benign familial neonatal-infantile epilepsy (BFNIE), severe developmental and epileptic encephalopathy (DEE) and intellectual disability (ID) to autism spectrum disorders (ASD). Yet, the underlying mechanisms are still incompletely understood. Methods To further elucidate the genotype-phenotype correlation of SCN2A variants we investigated the functional effects of six variants representing the phenotypic spectrum by whole-cell patch-clamp studies in transfected HEK293T cells and in-silico structural modeling. Results The two variants p.L1342P and p.E1803G detected in patients with early onset epileptic encephalopathy (EE) showed profound and complex changes in channel gating, whereas the BFNIE variant p.L1563V exhibited only a small gain of channel function. The three variants identified in ID patients without seizures, p.R937C, p.L611Vfs*35 and p.W1716*, did not produce measurable currents. Homology modeling of the missense variants predicted structural impairments consistent with the electrophysiological findings. Conclusions Our findings support the hypothesis that complete loss-of-function variants lead to ID without seizures, small gain-of-function variants cause BFNIE and EE variants exhibit variable but profound Nav1.2 gating changes. Moreover, structural modeling was able to predict the severity of the variant impact, supporting a potential role of structural modeling as a prognostic tool. Our study on the functional consequences of SCN2A variants causing the distinct phenotypes of EE, BFNIE and ID contributes to the elucidation of mechanisms underlying the broad phenotypic variability reported for SCN2A variants.